Search
Ask a question
0

The table shows the solution to the equation |2x – 3| - 1 = 2: Step 1 |2x – 3| = 2 + 1 Step 2 |2x – 3| = 3 Step 3 2x – 3 = 3 or 2x + 3 = 3 Step 4 2x = 6 or 2x

The table shows the solution to the equation |2x – 3| - 1 = 2:


Step 1 |2x – 3| = 2 + 1
Step 2 |2x – 3| = 3
Step 3 2x – 3 = 3 or 2x + 3 = 3
Step 4 2x = 6 or 2x = 0
Step 5 x = 3 or x = 0


Which is the first incorrect step?
Step 1

Step 3

Step 5

Solution is correct

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Elijah C. | Math, Science and Test Prep TutorMath, Science and Test Prep Tutor
5.0 5.0 (136 lesson ratings) (136)
1
The first incorrect step is step 3 because you have to distribute the negative making it -2x+3, not just 2x+3. 
Juan L. | All Levels of Algebra, Trigonometry, and Precalculus Tutor All Levels of Algebra, Trigonometry, and...
0
The incorrect step is the 3 you have to compare 2x - 3 to 3 and -3
2x-3 = 3 and 2x-3 = -3
x =3              x=0